Peran PKH Dalam Meningkatkan Kemampuan Suami Memberi Nafkah - Dermina Dalimunthe, Isa Yurida Tanjung Fatahuddin Aziz Siregar & (Jurnal El-Thawalib, 2020)
The Family Hope Program (PKH) began in 2007 and has been implemented in the Padangsidimpuan City area starting in 2013. And husbands who receive PKH still neglect their position as head of the family to carry out their obligations in the family, one of which is to provide a good living. Even when the family received PKH assistance, the husband did not use the assistance properly to be used as capital to open a business. As a result, families who receive PKH assistance are unable to improve the family's economy. Based on the above background, the purpose of this study is to find out how the Role of the Hope Family Program (PKH) in Increasing the ability of the Husband to Provide a Livelihood in Manunggang Jae Village and How to Increase the Ability of Husbands to Give a Livelihood after joining the Hope Family Program (PKH) in Manunggang Jae Village. The type of research used in this research is field research. Based on the results of the above research, the results show that the role of the hope family program in increasing the husband's ability and increasing the husband's ability after participating in the hope family program in Manunggang Jae village from the results of the interview with informants can be assessed that the hope family program plays an important role for the village community of Manunggang Jae and is capable increasing the husband's obligation to provide a living with the hope family program.